Elucidating the Lipid Binding Properties of Membrane-Active Peptides Using Cyclised Nanodiscs - Zhang, Alan H.; Edwards, Ingrid A.; Mishra, Biswa P.; Sharma, Gagan; Healy, Michael D.; Elliott, Alysha G.; Blaskovich, Mark A. T.; Cooper, Matthew A.; Collins, Brett M.; Jia, Xinying; Mobli, Mehdi (Frontiers in Chemistry, 2019)
The lipid composition of the cellular membrane plays an important role in a number of biological processes including the binding of membrane-active peptides. Characterisation of membrane binding remains challenging, due to the technical limitations associated with the use of standard biophysical techniques with available membrane model systems. Here, we investigate the lipid binding properties of two membrane active peptides, VSTx1, a well characterised ion-channel inhibitor, identified from spider venom, that preferentially binds to anionic lipid mixtures, and AA139 an antimicrobial -hairpin peptide, currently in pre-clinical development. The lipid binding properties of these peptides are elucidated using nanodiscs formed by both linear and sortase-mediated circularised forms of a membrane scaffold protein (MSP1D1ΔH5). We find that circularised nanodiscs are highly stable and insensitive to a number of common sample conditions (including lipid composition, a range of buffers, temperatures and concentrations). Using these circularised nanodiscs, we are able to extract detailed thermodynamic data using isothermal titration calorimetry (ITC) as well as atomic resolution mapping of the lipid binding interfaces of our isotope labelled peptides using solution-state, heteronuclear, nuclear magnetic resonance (NMR) spectroscopy. The thermodynamic parameters and binding interface derived for VSTx1 confirms previous studies using micelles and liposomes, establishing our approach as a suitable alternative to previous methods. The method was then applied to AA139, an antimicrobial peptide with unknown membrane binding properties. The characterisation of AA139, involved high-resolution structural characterisation in solution using NMR spectroscopy and the development of a suitable expression system for isotope labelling. AA139 was found to bind exclusively to anionic membranes with moderate affinity (Kd ~ low uM), and was found to have a lipid binding interface involving the termini of the b-hairpin structure. The described approach provides a general, fast and cost-effect method for investigation of the membrane binding properties of this important class of molecules.